Gunung Gangsir dan Wilayah di Sekitarnya - Ririet Surjandari (Borobudur, 2009)
Gunung Gangsir Temple, one of the glorious temple in East Java that made of bricks. There's two opinion about the period. One said that it is from Sindok's period, and the others said it is from Majapahit period. As we know, the architectur and decoration of the temple looks similarly with Prambanan Temple. The difference only on its material; Prambanan temple is made of stone, and Gunung Gangsir made of bricks with its unique size like plaque and big block. Gunung Gangsir Temple is around with amount of wells. Formerly, in 1993 there are 7 wells that function till that time. in 2007, that wells only 4 with 1 dry-well include. It is caused by the increasing people houses around Gunung Gangsir Temple. Temple and its environmental can be research by matching the data in the inscription with localization of three building that mentioned in that inscription.